Headspace gas concentrations of IODP Hole 386-M0084F - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Headspace (HS) gas concentrations of the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. Following standard protocols for headspace sampling, all headspace samples were collected onboard (offshore) from the base of each section immediately after section cutting following core recovery on deck. Two parallel headspace samples (IODP standard and requested samples) were collected from the bottom of every GPC core section, the longest core from each site, and the respective shorter trigger core. For each headspace double sample, ~5 cm^3 of sediment was collected (using two 2.5 cm^3 tip-cut syringes). Each 2.5 cm^3 headspace sample was then added to a 20 mL crimp vial with 5 mL of 1 M NaOH. After sealing, the samples were preserved at 4°C until analysis. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023